META-ANALISIS HUBUNGAN ORIENTASI RELIGIUS DENGAN PRASANGKA RASIAL - Baidi Bukhori (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2011)
Meta-analysis is motivated by research results that are not in the direction with the relationship of religious orientation of intrinsic, extrinsic, and fundamentalism by racial prejudice, and even sometimes there is evidence to the contrary. The purpose of this study is to integrate the results of research on the relationship of religious orientation of intrinsic, extrinsic, and fundamentalism with the racial prejudice that are so variative.The selection of the studies done in two ways: First, it is done manually, is by way of tracking through the Psychological Association (APA) or through journals in the library of the University of Gadjah Mada (UGM), University in Yogyakarta. Second, tracking the journals can be downloaded via EBSCO, ProQuest, SAGE, and thesis/dissertation obtained from the Networked Digital Library Theses and Dissertations on (NDLTD). Based on the tracking were found seventeen articles, consisting of 38 primary studies.In the analysis, these studies are combined because it was conducted by researchers and research subjects that are the same and the object of prejudice that is different. After the combination, the number of studies that analyzed became 35 studies, it consist of 13 intrinsic orientation, 12 extrinsic, and 10 of fundamentalism.The conclusion of these studies is that there is a negative relationship between intrinsic religious orientation with the racial prejudice, there is a positive relationship between the extrinsic religious orientation with the racial prejudice, and there is a positive relationship between the orientation religious fundamentalism with the racial prejudice.